Herbal For Anxiety In Psychology Case: Bibliometric Analysis - Salsabila Shafiya; Irma Finurina Mustikawati; Paramita Septianawati; Glorio Immanuel (Jurnal Health Sains, 2024)
This research aims to carry out an in-depth analysis of the effects of herbs on anxiety in psychological cases. In order to address the complex character of anxiety disorders, there is a link between herbal therapies for anxiety in psychological cases and the integration of psychological and herbal viewpoints. Herbal treatments provide supplementary options for modifying neurobiological mechanisms underpinning symptom presentation, whereas psychological therapies focus on the cognitive, emotional, and behavioural elements of anxiety. Bibliometric analysis was done using VOSviewer software, and data was taken from the Scopus database. Data was taken by searching for keywords that were appropriate to this research, namely "herbal,” “anxiety,” and “psychology.”Herbal remedies are a viable means of supplementing psychological therapy and fostering overall well-being while reducing anxiety in psychological problems. In psychological circumstances, the link between herbal therapies for anxiety entails integrating herbal and psychological viewpoints to address the intricate interaction of behavioural, affective, cognitive, and neurobiological components that underlie anxiety disorders. Healthcare professionals should stay up to date on the growing body of research supporting herbal therapies and participate in collaborative decision-making with patients on available treatments, taking into account each patient's unique preferences, values, and cultural beliefs. The research's methodological approach, which combines bibliometric analysis with data retrieved from the Scopus database, offers a methodical and objective way to compile the body of knowledge on herbal remedies for anxiety in psychiatric problems.